Assessment of uterine caruncles, uterine cervix, and vulva during the postpartum period in Kivircik ewes with shear-wave elastography - Uçmak, Zeynep Günay; Kurban, İbrahim; Uçmak, Melih; Özbezek, Mehmet Fatih; Kılıçarslan, Mehmet Ragıp; Duro, Sokol; Szara, Tomasz; Gündemir, Ozan (Frontiers in Veterinary Science, 2024)
IntroductionThis study aims to quantify the shear wave speed (SWS) and stiffness of the uterine cervix (close to the internal cervical ostium (IOC) which is the cranial portion of cervix and close to the external cervical ostium (EOC) which is the caudal portion of cervix), caruncular areas, and vulvar labia during the postpartum period in healthy Kivircik ewes by using shear-wave elastography. Power Doppler ultrasonography was performed to evaluate the color pixel percentage (CPP) of the caruncles.MethodsThe study included 13 healthy pregnant Kivircik ewes, which were randomly selected. A total of 12 measurements were taken from the uterine cervix and vulva from the postpartum first day to PP42 (daily for the first week and weekly from PP14 to PP42). However, only eight measurements were obtained from the caruncles because they could not be visible after day 14.ResultsThe time-dependent differences in the widest cross-sectional diameter of the caruncles were statistically significant (p < 0.001) both in ewes giving birth to singletons and twins. As a result of power Doppler ultrasonography examination, the time-dependent differences in the CPP of the caruncles were statistically significant (p < 0.01) in ewes giving birth to both singletons and twins. The diameter of the cervix at PP3 was significantly higher than the ones at PP14, PP21, PP28 (p < 0.05). The SWS and stiffness in the IOC for all ewes at PP35 were significantly higher than the ones at PP1, PP4, PP7, and PP14 (p < 0.05 and p < 0.01; respectively). However, the time-dependent differences in SWS and stiffness in the EOC were not statistically significant (p > 0.05). The time-dependent differences in the SWS and stiffness in the vulva were statistically significant (p < 0.001) in ewes giving birth to both singletons and twins.DiscussionIn conclusion, it is possible to describe the changes throughout the postpartum period and evaluate the involution of the uterine cervix, caruncles, and vulvar labia and tissue stiffness with significant results by B mode ultrasonography, power Doppler and shear wave elastography. We provided valuable information to elucidate the differences in the involution process of the uterine cervix, caruncles, and vulva concerning the number of offspring during the postpartum period in Kivircik ewes.